2017
DOI: 10.2174/1876386301710010005
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapy Interventions and the Outcomes for Complex Regional Pain Syndrome (CRPS) Type 1 on the South Island of New Zealand – A Longitudinal, Prospective Case Series

Abstract: Physiotherapy is considered in pain medicine to be a key element in the management of Complex Regional Pain Syndrome (CRPS). This is the first paper to document and categorise all physiotherapy intervention methods used as well as evaluate the outcomes of a case series of 18 CRPS patients attending physiotherapy in a prospective, longitudinal study across a region. Outcomes were measured across the region of the South Island of New Zealand over 1 year through independent telephonic interviewing of the pain exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Since CRPS lacks identifiable histopathologic or biochemical indicators, a clear and accurate description is required. CRPS is frequently diagnosed by exclusion, relying mainly on clinical examination and bone scans [ 9 ]. When seeking medical attention for shoulder pain, it is important to assess its location, nature, severity, onset, and duration, as well as any potential risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Since CRPS lacks identifiable histopathologic or biochemical indicators, a clear and accurate description is required. CRPS is frequently diagnosed by exclusion, relying mainly on clinical examination and bone scans [ 9 ]. When seeking medical attention for shoulder pain, it is important to assess its location, nature, severity, onset, and duration, as well as any potential risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Pons (2019) of the physiotherapy management of CRPS found that fractures were the inciting event for CRPS in 42% of patients, followed by soft tissue injury (36%), and surgery (21%). The incidence of CRPS reported in this study was low (0.8%).…”
Section: Discussionmentioning
confidence: 99%